Fatal Blunt Severe Hemorrhagic Pancreatitis Trauma: A Case Report - Lestari, Viny Agustiani; Setya Aji Priyatna; Didik Mulyono (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Pancreatic trauma is a rare but potentially fatal condition. Blunt pancreatic trauma can lead to severe hemorrhagic pancreatitis, a life-threatening complication. This case report presents a fatal instance of blunt severe hemorrhagic pancreatitis resulting from an assault. Case presentation: A 21-year-old male victim was found unconscious in a student dormitory after suffering multiple punches to the abdomen during an assault. Despite being rushed to the hospital, the victim succumbed to his injuries. A post-mortem examination revealed extensive bruising on the abdomen, along with internal injuries including cardiovascular enlargement, colonic vasodilation, and blood on the surface of the pancreatic tissue. Histological analysis of the pancreas showed severe necrosis, cytoplasmic necrosis, and widespread hemorrhagic hyperemia of the peripancreatic tissue. Toxicological tests for drugs, alcohol, and other substances were negative. Conclusion: This case highlights the potential severity of blunt pancreatic trauma and the importance of prompt diagnosis and treatment. The retroperitoneal location of the pancreas can make diagnosis challenging, leading to delays in care and potentially fatal outcomes. In cases of suspected abdominal trauma, a thorough examination of the pancreas is crucial, including histological analysis if necessary. This case underscores the need for increased awareness of pancreatic trauma among healthcare professionals and the public.